Non-take-up of student financial aid—A microsimulation for Germany. Issue 1 (2nd January 2019) - Herber, Stefanie P.; Kalinowski, Michael
ABSTRACT: We estimate the percentage of eligible students who do not take up their federal need-based student financial aid entitlements in a microsimulation model for the German Socio-Economic Panel Study 2002–2013. We find that about 40% of the eligible low-income students do not take up their entitlements. Non-take-up is inversely and rather inelastically related to the level of benefits. We investigate possible reasons for non-take-up, accounting for potential sample selection and endogeneity issues; and discuss policy implications.